Hubungan Antara Motivasi Berprestasi Dengan Kepuasan Kerja Pada Pegawai RSUD Dr. Sayidiman Magetan - Gastriawan Prakoso, Alfa, Achmad Dwityanto, S.Psi, M.Si (2016)
The aim of this research is to know is there a relationship between achievment motivation and work satisfaction on RSUD dr. Sayidiman Magetan employees. The hypothesis proposed that there are positive relathionship between achievment motivation and work satisfication on RSUD dr. Sayidiman Magetan employees. Researcher used purposive sampling to determine the subjects of research, there are 85 respondents. This research used quantitative methods with achievment motivation scale and work satisfication scale as a measurement. Data analysis on this research using SPSS 19.0 with product-moment correlation method, obtained 0,536 of coreelation coeffisien and 0,000 (p≤0,01) of significant (p) which showed that there is a positive relationship between achievment motivation and work satisfaction. Effective donation from two variable showed by R2 = 0,287 it means achievment motivation affects by 28,7% to work satisfication and there is 71,3% affected by other. Achievment motivation on RSUD dr. Sayidiman employees relatively high with empirical average (EA) = 123,62 and hypothetical average (HA) = 105. Work satisfication on RSUD dr. Sayidiman employees relatively high with empirical average (EA)= 138,7 and hypothetical average (HA) = 117,5. Keyword : Achievment Motivation, Work Satisfication.